2007
DOI: 10.1097/01.olq.0000258485.23066.a6
|View full text |Cite
|
Sign up to set email alerts
|

Sexually Transmitted Infections and Sexual Practices in Injection Drug Users and Their Regular Sex Partners in Chennai, India

Abstract: Reaching out to IDUs and their female regular sex partners with modified STI management guideline and promoting women-controlled safer sex measures are needed harm-reduction measures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
16
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 11 publications
0
16
1
Order By: Relevance
“…20 A study conducted among high-risk women in Western India found similar rates of trichomoniasis and chlamydia as this study, but much higher rates of N. gonorrhea. 13 Recent studies conducted in western and southern India have identified a high prevalence of HSV-2 14 , 15 However, an earlier multination study among antenatal clinic patients found relatively lower rates of HSV-2 among Indians with Indian women having lower rates of HSV-2 than their male counterparts. 9 In addition to unprotected sexual intercourse, STIs have been shown to be independent facilitators of HIV transmission and acquisition.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…20 A study conducted among high-risk women in Western India found similar rates of trichomoniasis and chlamydia as this study, but much higher rates of N. gonorrhea. 13 Recent studies conducted in western and southern India have identified a high prevalence of HSV-2 14 , 15 However, an earlier multination study among antenatal clinic patients found relatively lower rates of HSV-2 among Indians with Indian women having lower rates of HSV-2 than their male counterparts. 9 In addition to unprotected sexual intercourse, STIs have been shown to be independent facilitators of HIV transmission and acquisition.…”
Section: Discussionmentioning
confidence: 99%
“…8,10 In India, the prevalence of HIV remains relatively low at 0.91%. 2 Recent studies conducted in different parts of India have documented high rates of STIs within various groups, such as men who drink alcohol and engage in high-risk behavior, 11 men who have sex with men, 12 female sex workers, 13 and injection drug users 14 as well as individuals attending STI clinics 15,16 ; however, there is a dearth of longitudinal data on the development of STIs. 17 Given the synergistic transmission of STIs and HIV, the present study was undertaken to determine the prevalence and incidence of different STIs and to delineate the risk factors associated with STI transmission among individuals who were identified to be at increased risk for HIV infection in Chennai, India.…”
mentioning
confidence: 99%
“…Some studies in India have used outreach methods to recruit the female partners of men who inject drugs for research and HIV prevention interventions (Panda et al 2007a;Vijayalakshmi et al 2004), however the involvement of these men to gain access to their partners is not clear. Non-governmental organizations working with people who inject drugs may consider using community health workers to implement targeted information, education and communication messages through community events to reach these women directly.…”
Section: Discussionmentioning
confidence: 98%
“…The north-eastern states have a long history of drug abuse and a rapid spread of HIV and HCV infection among the IDUs [23][24][25][26]. Drug abusers, under the influence of drugs, invariably indulge in high-risk behaviours such as unsafe sex and needle sharing, which has contributed to the spread of HIV and Hepatitis C to their sex partners [27][28][29][30][31]. These periodic studies indicated that the rates of HIV and HCV positivity are rapidly increasing among this risk group.…”
Section: Discussionmentioning
confidence: 99%